2016
DOI: 10.1016/j.chb.2015.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Perceived derived attributes of online customer reviews

Abstract: The influence of online customer reviews (OCRs) on customers' purchase intention has recently gained considerable attention, in both academic and business communities. Technology allows customers to freely and easily post their comments and opinions online about any product or service; this type of customer review can have a significant effect on customers' purchase decisions. Previous studies, however, have mainly focused on the influence of the virtual attributes of OCRs such as volume and valence on consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
135
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 106 publications
15
135
1
15
Order By: Relevance
“…Among the models explaining the determinants of behavioral intentions, the theory of reasoned action (Fishbein & Ajzen, 1975) and its extensions are considered robust models in a wide variety of contexts, including e-commerce (Elwalda et al, 2016;Ha & Janda, 2014;Pavlou & Fygenson, 2006). One advantage of this theory is that it includes cognitive components such as attitudes, which are known to direct human judgments and behaviors.…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the models explaining the determinants of behavioral intentions, the theory of reasoned action (Fishbein & Ajzen, 1975) and its extensions are considered robust models in a wide variety of contexts, including e-commerce (Elwalda et al, 2016;Ha & Janda, 2014;Pavlou & Fygenson, 2006). One advantage of this theory is that it includes cognitive components such as attitudes, which are known to direct human judgments and behaviors.…”
Section: Research Modelmentioning
confidence: 99%
“…For instance, Fishbein and Ajzen (1975, p. 368) state, "if one wants to know whether or not an individual will perform a given behavior, the simplest and probably most efficient thing one can do is to ask the individual whether he intends to perform that behavior". As a result, online purchase intention becomes a crucial factor that can predict the effectiveness of online stimuli (Amaro & Duarte, 2015;Elwalda et al, 2016;Lu, Fan, & Zhou, 2016;Wu et al, 2008).…”
Section: Online Purchase Intention (Opi)mentioning
confidence: 99%
“…Kala and Chaubey (2018b) also found that electronic word of mouth communication influences the purchase intention towards lifestyle products in India. Elwalda et al (2016) examined the influence of online social media reviews on consumers' purchase intentions, and confirmed quality, perceived usefulness, and credibility of reviews influence customer purchase intention. A recent study of Shah et al (2019) also empathized that social media has become a preferred means of direct communication with young customers and the rapid proliferation of such form of information significantly influence their purchasing behavior.…”
Section: Social Media Marketing and Purchase Intentionmentioning
confidence: 99%
“…These criteria are marked with a horizontal line in the confusion matrix. The additional guidelines and their associated criteria have also been mentioned in previous studies [35,36]. However, these studies used self-reporting approach rather than an evaluation approach.…”
Section: 59%mentioning
confidence: 99%